Commedia dell’Arte Masks in Giorgio Strehler’s Performances - Baldina Yuliya А. (Художественная культура)
The article aims to retrace the theatrical interpretation of Carlo Goldoni’s (1707–1793) works carried out by the founder of the Piccolo Theatre in Milan, the outstanding Italian theatre director Giorgio Strehler (1921–1997). The phenomenon of commedia dell’arte is analysed not in the historical and theatrical context of its origin and existence but as a dramatic basis for the reform undertaken by the 18th century Venetian playwright, which was comprehended and presented from various perspectives in the 20th century director’s theatre. The article analyses Strehler’s production of Goldoni’s The Servant of Two Masters. The performance in its ten director’s editions reflected the key stages in the evolution of the master’s staging method and his creative search in the field of mask theatre, the art of pantomime, the realistic, the epic and, finally, metatheatre.